FLEXING SEBAGAI HABITUS: ANALISIS PRAKTIK SOSIAL PEREMPUAN BUGIS DI KECAMATAN MARITENGNGAE, KABUPATEN SIDRAP - Aisyah Yulindasari; Buchari Mengge; Ridwan Syam (Yayasan Literasi Sains Indonesia, 2024)
This qualitative research examines the social practice of flexing among Buginese women in Maritengngae District, Sidrap Regency, aiming to uncover how Buginese women engage in the social practice of flexing and its social impacts. The research was conducted over 4 months, collecting data through semi-structured interviews and analyzing data using data reduction, data presentation, and conclusion drawing. The results show that the social practice of flexing among Buginese women in Sidrap is influenced by cultural factors, family, desire to enhance appearance, display social status, and follow trends. The findings reveal that the social practice of flexing has become part of the habitus of the Sidrap community by utilizing economic, social, and symbolic capital to achieve social status, and it impacts changes in values, norms, lifestyle, individual identity, community perception, and social inequality. This research is essential to understand the complex social practice of flexing among Buginese women in Sidrap, which is closely related to socio-cultural factors, despite limitations in the scope of the area and qualitative methods. Therefore, it is recommended to expand the scope and methodological approaches for further research to gain a more comprehensive understanding.